Local partnership as a tool for stimulating the development of rural areas of Ukraine - Verbivska, Liudmyla; Зибарева, Оксана Василівна; Шилепницький, Павло Іванович; Белей (Belei), Cвітлана (Svitlana) (My University, 2020)
The scientific research deals with the ways and strategies of using local partnerships to address the challenges of rural development. These include the advantages and economic, law-based and social restrictions as well as the principles of using local partnerships for rural development of Ukraine. The main economic benefits raise due to the aggregated resources, cooperation activities, risk reduction, employment and diversification of income and expenditures of the population. The advantages of local partnerships implementation lie in the application of the normative framework that is efficient for the project’s implementation and promotion of the rural growth, in its continuous improvement, in support of the local projects by international organizations on the international level. Social advantages of the local partnerships are determined by its usage as the base for innovations on the rural areas with the aims to improve the welfare, solve common local issues, gain the advanced experience, provide informative communicative systems and informative resources and secure the interests of local societies at the national level. The selective character of local partnership projects, low-informative level and insufficient support of local authorities, insufficient development of informative communicative systems in the rural areas that lower the mobility level of some factors of production and have negative impact on the welfare – all determine restrictions of using local partnerships at the national level. The main reason to use the local partnership for stimulating the rural growth in Ukraine is to support the adaptations to changes in the agrarian sector, united communities, environment, welfare affected by European integration. Among the principles of the local partnership implementation on all rural areas of Ukraine are openness, equal rights of all partners, indifference to politics, accuracy and transparence, activity and integration, common economic and social responsibility of partnership. The paper examines stages of the successive local partnership implementation on rural areas: diagnosis of the interests of stakeholders and environment, partnership planning, strategic grounds for partnership, partnership implementation, monitoring the stages of partnership and quality of the results by precise criteria, strategic partnerships support a wide and flexible range of activities for the long-term period.
Keywords: public-private partnership, cooperation, economic security, financial support.